OKSIDASI SIKLIK PADA TEMPERATUR 1200 oC PADUAN TERNER Ni-Al-Ti YANG DIDOPING DENGAN WOLFRAM - Aprilianda, Adam; Ambardi, Pradoto; Prajitno, Djoko Hadi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
This research is aimed to study the effect of Wolfram (W) on high temperature oxidation resistance of Ni-Al-Ti ternary alloy by cyclic oxidation method at 1200 °C. The amount of Wolfram added was 1.5% W. Number of samples used in this study is 2 samples, namely Ni-Al-Ti alloy and Ni-Al-Ti-1.5W alloy. Cyclic oxidation process was carried out with cycle variation of 4, 9, 16 and 25 cycles (a cycle refers 60 minutes of heating in the furnace and 30 minutes cooling outside the furnace). The tests include Rockwell-C hardness testing, metallographic testing, oxide thickness testing, surface morphology observation, Scanning Electron Microscopy (SEM) examination and X-Ray Diffraction (XRD) analysis. Wolfram content shows an influence in the hardness values with the highest hardness value obtained for the Ni-Al-Ti-1,5W sample with a hardness of 48.5 HRC for as cast sample and 50.5 HRC after treatment solution. The addition of wolfram appears to improve the resistance to high temperature, which can be seen from the cyclic weight loss curve where the Ni-Al-Ti-1,5W sample has lower weight loss when compared to the other sample.